Degradation of histamine by Bacillus polymyxa isolated from salted fish products - Yi‐Chen Lee; Chung‐Saint Lin; Fang-Ling Liu; Tzou‐Chi Huang; Yung‐Hsiang Tsai (2015)
Histamine is the causative agent of scombroid poisoning, a foodborne chemical hazard. Histamine is degraded by the oxidative deamination activity of certain microorganisms. In this study, eight histamine-degrading bacteria isolated from salted fish products were identified as Rummeliibacillus stabekisii (1 isolate), Agrobacterium tumefaciens (1 isolate), Bacillus cereus (2 isolates), Bacillus polymyxa (1 isolate), Bacillus licheniformis (1 isolate), Bacillus amyloliquefaciens (1 isolate), and Bacillus subtilis (1 isolate). Among them, B. polymyxa exhibited the highest activity in degrading histamine than the other isolates. The ranges of temperature, pH, and salt concentration for growth and histamine degradation of B. polymyxa were 25-37°C, pH 5-9, and 0.5-5% NaCl, respectively. B. polymyxa exhibited optimal growth and histamine-degrading activity at 30°C, pH 7, and 0.5% NaCl in histamine broth for 24 hours of incubation. The histamine-degrading isolate, B. polymyxa, might be used as a starter culture in inhibiting histamine accumulation during salted fish product fermentation.